PEMBELAJARAN IPS BERBASIS KEARIFAN LOKAL SUKU BADUY UNTUK MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN PESERTA DIDIK SEKOLAH DASAR - Fazri Yulianto; Lili Fajrudin; Lucyana Lucyana (LPPM Universitas Bina Bangsa, 2023)
The process of growing the character of students can be done by the teacher through the learning process, namely social studies learning. Teachers can design Social Studies learning by incorporating local wisdom values ​​in the material provided as an effort to grow the character of students, for example, the local wisdom values ​​of the Baduy Tribe. This study aims to integrate the local wisdom values ​​of the Baduy Tribe in social studies learning to foster students' environmental care character. Social studies learning based on local wisdom values ​​of the Baduy tribe is carried out because the Baduy people have a character of concern for the environment that students can emulate and implement in their daily lives. This research is quantitative research with research subjects namely class IV students totaling 30 students. The trials in this study were carried out in two stages, the first stage was carried out to obtain initial data (pretest), and the second stage was carried out to obtain data on the growth of students' environmental care character after conducting IPS learning based on local wisdom values ​​of the Baduy Tribe (post-test). Based on the research results, the initial data (pretest) obtained an average result of 67.25, while the average result (post-test) after social studies learning based on local wisdom values ​​of the Baduy tribe was 79.7667. Based on the results of the study it can be concluded that social studies learning based on local wisdom values ​​of the Baduy tribe can foster students' environmental care character